Childhood Maltreatment Influences Mental Symptoms: The Mediating Roles of Emotional Intelligence and Social Support - Zhao, Jiaxu; Peng, Xin; Chao, Xiaomei; Xiang, Yanhui (Frontiers in Psychiatry, 2019)
Childhood maltreatment and its influence on mental health are key concerns around the world. Previous studies have found that childhood maltreatment is a positive predictor of mental symptoms, but few studies have been done to explore the specific mediating mechanisms between these two variables. Previous studies have found that there is a negative correlation between childhood maltreatment and emotional intelligence and between childhood maltreatment and social support, both of which are strong indicators of mental symptoms. Therefore, in this study, we took emotional intelligence and social support as mediating variables, exploring their mediating effects between childhood maltreatment and mental symptoms via the structural equation modeling method. We recruited 811 Chinese college students to complete the Childhood Trauma Questionnaire (CTQ), the Symptom Checklist 90 Scale (SCL-90), the Wong Law Emotional Intelligence Scale (WLEIS), and the Perceived Social Support Scale (PSSS). The results showed a significant and positive correlation between childhood maltreatment and mental symptoms (β = 0.26, P < 0.001); meanwhile, social support played a significant mediating role in the influence of childhood maltreatment on emotional intelligence [95% confidence intervals, (−0.594 to −0.327)]; and emotional intelligence likewise played a significant mediating role in the effect of social support on mental symptoms [95% confidence intervals, (−0.224 to −0.105)]. These results indicated that childhood maltreatment not only directly increases the likelihood of developing mental symptoms, but also affects emotional intelligence through influencing social support and then indirectly increasing the likelihood of developing mental symptoms. This study provided a theoretical basis for ameliorating adverse effects of childhood maltreatment on mental symptoms by enhancing emotional intelligence and social support.